2015
DOI: 10.1016/j.apenergy.2015.05.120
|View full text |Cite
|
Sign up to set email alerts
|

Illuminated but not electrified: An assessment of the impact of Solar Home System on rural households in South Africa

Abstract: 8The introduction of the off-grid electrification program in South Africa using the Solar Home System (SHS) 9 was a central component of the government policy aimed at bringing development to un-electrified 10households. An assessment of the performance of SHS in many countries provided little evidence to support 11 the development impact of the system. The general perception is that the SHS program is wasting 12 government funds and has no hope of achieving the set objectives. Previous scientific reports have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…Off-grid solar solutions like SHSs have been at the heart of the electrification strategy of some African governments in order to extend electricity access to the most inaccessible areas, especially in countries like Mali and Burkina Faso, where standout results have been achieved thanks to donors and results-based financing. Nevertheless, in South Africa households do not want to be included in SHS programs for fear of being classified as electrified, thereby risking exclusion from future introductions of more efficient technologies or expansion of the grid (Azimoh et al, 2015).…”
Section: Quality Of Productsmentioning
confidence: 99%
“…Off-grid solar solutions like SHSs have been at the heart of the electrification strategy of some African governments in order to extend electricity access to the most inaccessible areas, especially in countries like Mali and Burkina Faso, where standout results have been achieved thanks to donors and results-based financing. Nevertheless, in South Africa households do not want to be included in SHS programs for fear of being classified as electrified, thereby risking exclusion from future introductions of more efficient technologies or expansion of the grid (Azimoh et al, 2015).…”
Section: Quality Of Productsmentioning
confidence: 99%
“…SHSs have been widely explored as an alternative and cost-effective option for rural electrification (Bhattacharyya, 2016;Scott and Miller, 2016;Chaurey et al, 2012;Lighting Africa, 2011;Lemaire, 2011;Jacobson, 2004). On one hand the scale-up of solar systems have been successful in Bangladesh with over 2.6 million SHS's installations covering 9% of the electricity demand (IRENA, 2014), but on the other hand SHS programmes in Namibia, South Africa and Papua New Guinea have had limited success due to a combination of factors such as logistics, lack of training, incorrect design and installation, and lack of customer service and maintenance (Sovacool et al, 2011;Azimoh et al, 2015) There are a wide range of solar home technologies available in the market and consumers have a mixed level of satisfaction with regards to maintenance and performance of the systems (Urpelainen, 2016). There is a need for solutions which can optimise the design and performance of SHS's based on energy requirements of the end-user, enable private companies to offer improved maintenance services and improve installation and subsequent monitoring (Campana et al, 2016).…”
Section: Research Gapsmentioning
confidence: 99%
“…The field interviews conducted in this study in Namibia revealed that the investigated SHSs installations were not performed properly. The main problems included incorrect design and installation that result in unsatisfied end-users, which was also highlighted in a study conducted by Azimoh et al in South Africa [16]. The wrong design and installation was mainly due to two different aspects: the first was related to an inaccurate load estimation that most of the time is bounded to the limited awareness of the end-users on their own actual electricity consumption; the second was related to the service providers which have limited knowledge of solar power systems and in general a limited technical know-how [17].…”
Section: Shss Programmes Have Been Used As a Viable Solution For Starmentioning
confidence: 86%